Asuhan Keperawatan Keluarga Tn. A Khususnya Ny. B Dengan Pemberian Kompres Serai Hangat Pada Penderita Rheumatoid Artritis Di Desa Naumbai Wilayah Kerja Upt Puskesmas Air Tiris Tahun 2022 - Tinur, Risna Delram; Indrawati, Indrawati; Hamid, Afriadi (El-Emir Institute, 2025)
Rheumatoid Arthritis is a condition experienced by sufferers in which inflammation occurs in the bones or joints. Rheumatoid Arthritis can disrupt activities and even cause paralysis. The intervention that can be done is by giving a warm lemongrass compress. This is because lemongrass contains an enzyme, namely the cyclo-oxygenase enzyme which can reduce inflammation that is absorbed through the skin in the inflamed/swollen area, while a warm compress on the body area will send a signal to the hypothalamus to be stimulated, the effector system emits a signal that starts sweating and peripheral vasodilation. Changes in the size of blood vessels are regulated by the vasomotor center in the medulla oblongata of the brain stem, under the influence of the anterior hypothalamus so that vasodilation occurs. The occurrence of this vasodilation causes blood flow to each tissue to increase, especially those experiencing inflammation and pain, so that there is a decrease in joint pain in the inflamed tissue. This study was conducted in November 2021, then analyzed the data and carried out interventions from the diagnosis obtained. The nursing diagnoses that emerged were chronic pain related to the family's inability to care for sick family members, ineffectiveness of family health management related to lack of family knowledge about rheumatoid arthritis, and anxiety related to lack of family knowledge in recognizing the problem. Warm lemongrass compresses were given for 3 consecutive days and given twice a day, namely in the first 10 minutes and one hour later, another compress was given for 10 minutes. Results: nursing problems can be resolved because the client said the pain was reduced and the client could return to activities. Conclusion: giving warm lemongrass compresses has a positive impact on the client so that it can reduce the scale of pain in Mrs. B with Rheumatoid Arthritis.